Saccharomyces Cerevisiae as a Tool to Evaluate the Effects of Herbicides on Eukaryotic Life - Braconi, Daniela; Bernardini, Giulia; Millucci, Lia; Jacomelli, Gabriella; Micheli, Vanna; Santucci, Annalisa (IntechOpen, 2011)
None